Analisis Pengaruh Pemberian Kredit terhadap Kinerja Debitur Mikro: Kasus pada ULM ABC, PT Bank XYZ di Jakarta - Hasan Supriadi; Musa Hubeis; Illah Sailah (Institut Pertanian Bogor, 2007)
One way to support an attempt to activate reel sectors of national economy is by empowering the roles of micro entrepreneurs. Such empowerment can be employed by providing guidance, direction, and assistance so that fundamental problems slowing down the growth of micro entrepreneur empowerment can be overcome. One of the basic problems generally faced by micro entrepreneurs is the problem of finance or source of financing. The objectives of this study are to find out whether financing or credit provision from the Micro Service Unit (MSU) of ABC to micro entrepreneurs can improve the performance of micro entrepreneurs, and to identify the schemes of credit provision from the MSU of ABC to micro entrepreneurs and their problems in the field. The methods used in this study were direct observation to the field and questionnaires distributed to 40 selected respondents of micro entrepreneurs who have been debtors of the MSU of ABC and of those 40 respondents, 34 were selected, especially those who got the facility to obtain productive credit. The data of the selected respondents were analyzed using SPSS 11.0 program to analyze the correlation and to find out the impact of credit provision on the performance of micro entrepreneurs. The type of data in this study was those of ratio and they were analyzed statistically using pair t-test or t-test with a significant level of 5%. The results of the analysis show that on the significant level of 5%, the average result of Profit Margin (PM) after the credit provision increased significantly compared to that before the credit provision; there was no significant decline in the average Return on Asset (ROA) after the credit provision compated to that before the credit provision; there was a really significant increase on the average of Return on Equity (ROE) after the credit provision compared to that before the credit provision; the average of Asset after the credit provision increased quite significantly compared to that before the credit provision; and the average sales after the credit provison increased significantly compared to that before the credit provision. The results on the study on the schemes of credit provision as reflected on features of credit products of the MSU show that all the features of credit products of the MSU are aflopen in nature (with the maximum credit declining periodically based on the schedule) with the minimum duration of 1 (one) year. The results of the observation on the field show that the financing need of the micro entrepreneurs is transactional in nature or seasonal with the duration of between 1 and 6 months not having been accommodated in the product features of the MSU of ABC, PT. Bank XYZ.